F(x) = 1/(x+2) & g(x) = x/(x-3)
(f(x) + g(x) = 1/(x+2) + x/(x-3). Reduce to same denominator:
1/(x+2) + x/(x-3) =(x-3) + x(x-3)/(x+2).(x-3) ==> (x²+3x-3)/(x+2).(x-3)
B) 64, because all these numbers have a difference of 14, and it you keep going, the 10th term will be 64.
Answer:
(4,0)
Step-by-step explanation:
It is a linear function so you find the slope by doing y2-y1/x2-x1 and you find the slope to be 1/2. You can then setup an equation using it and graph it to find the next value.
Answer:
Coordinates: (2, -1)
Part A
X coordinate is positive
Y coordinate is negative
Part B
Coordinates after Y-axis reflection: (-2, -1)
X coordiate is negative
Y coordinate is negative
Good luck!
F - g(2) = 3x^2 + 1 - ( 1 - x )
= 3x^2 + 1 - 1 + x
= 3x^2 + x
= 3(2)^2 + 2
= 14
the answer is B.14
i am a mathematics teacher. if anything to ask please pm me